INCEPTSIOL SOIL FERTILITY STATUS ON PT. PALM PALM PLANTATIONS. DYNAMICS OF MULTI INITIATIVES IN SEMITAU DISTRICT, KAPUAS HULU DISTRICT - Florensius Irwan Afendy; Rita Hayati; Bambang Widiarso (Fakultas Pertanian, Universitas Janabadra, 2024)
ABSTRACTThis research aims to determine the soil fertility status and provide fertilizer recommendations based on the soil fertility status of inseptisol on PT's oil palm plantations. Multi Initiative Dynamics. The research starts from October 9, 2023 to December 13, 2022 and until the results are presented. Disturbed soil sampling was carried out in each block using the diagonal method. In 1 block, 3 sub-blocks are created. For each sub-block, 5 soil sampling points were determined for oil palm plantations and 1 composite soil sample was obtained from each sub-block, so that in 1 block 3 composite soil samples were obtained which were used for soil chemical analysis. The distance of the soil sampling point is 1.5 meters from the oil palm tree. Soil sampling points were disturbed by drilling at a depth of 0-30 cm and intact soil samples were taken using a sample ring at a depth of 0-30 cm in oil palm plants. For each block, 3 intact soil sampling points were determined to represent each research location, thereby obtaining 9 intact soil samples which were used for soil bulk weight analysis. The variables observed in this research are, soil reaction (soil pH), C-Organic N-Total, P-Available, K-dd, P-Total, K-Total, CEC, KB, and Al Saturation, supporting variables for Texture analysis soil, Soil Profile, and Soil bulk weight. Research results The soil type in the observation area is classified as Inseptisol soil type, the soil texture in blocks E21, F21 and F26 has a clay and sandy loam texture class, the soil reaction (pH) in blocks E21, F21 and F26 has acid criteria. The C-Organic content in blocks E21, F21, F26 has low and medium criteria. The N-total content in blocks E21, F21, F26 has low criteria. The P-Available content in blocks E21, F21, F26 has very low criteria. The P-total content in blocks E21, F21, F26 has a very low average criterion. K-dd in blocks E21, F21, F26 have very low, low and medium criteria. K-total in blocks E21, F21, F26 has very low and low criteria. Cation Exchange Capacity (CEC) in blocks E21, F21, F26 has low criteria. The base saturation of blocks E21, F21, F26 has very low criteria. Al saturation in blocks E21, F21, F26 has very low criteria. Recommendations for Urea, SP-36 and MOP (KCL) fertilization at the research location, namely Block E21, are 271.7 kg/ha, 104.39 kg/ha and 39.35 kg/ha, Block F21 is 298.87 kg/ha, 287.43 kg/ha and 245.61 kg/ha, Block F26 is 360.36 kg/ha, 177.32 kg/ha and 145.58 kg/ha.Keywords: Soil Fertility Status, Soil Inceptisol and Fertilizer Recommendations.